2016
DOI: 10.1002/clc.22654
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and outcomes associated with atrial fibrillation observed during acute coronary syndrome: Real‐world data from the Acute Coronary Syndrome Israeli Survey (ACSIS), 2000–2013

Abstract: Background The past decade has brought major advances in therapy of patients presenting with acute coronary syndromes (ACS). Hypothesis The outcomes of ACS patients with atrial fibrillation (AF) has improved over the years. Methods We evaluated time‐dependent changes in clinical characteristics, management strategies, and outcomes associated with AF observed during ACS hospitalization in patients enrolled in the biannual ACS Israeli Surveys (ACSIS) between 2000 and 2013. We divided the surveys into early (2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
1
21
0
2
Order By: Relevance
“…The results of our systematic review and meta‐analysis, which included high‐quality prospective cohort studies, for the first time clearly showed the increased risk of all‐cause mortality rates and MACE in patients with coexisting AF and symptomatic PAD. These findings are in line with previously published meta‐analyses on the prognostic role of AF in CAD . As warfarin and other vitamin K antagonists are known to increase vascular calcification and calcification of coronary arteries, future trials are needed to evaluate the potential benefit of direct oral anticoagulants in patients with atherosclerotic vascular disease and AF …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of our systematic review and meta‐analysis, which included high‐quality prospective cohort studies, for the first time clearly showed the increased risk of all‐cause mortality rates and MACE in patients with coexisting AF and symptomatic PAD. These findings are in line with previously published meta‐analyses on the prognostic role of AF in CAD . As warfarin and other vitamin K antagonists are known to increase vascular calcification and calcification of coronary arteries, future trials are needed to evaluate the potential benefit of direct oral anticoagulants in patients with atherosclerotic vascular disease and AF …”
Section: Discussionsupporting
confidence: 87%
“…These findings are in line with previously published meta-analyses on the prognostic role of AF in CAD. 4,5,22 As warfarin and other vitamin K antagonists are known to increase vascular calcification and calcification of coronary arteries, future trials are needed to evaluate the potential benefit of direct oral anticoagulants in patients with atherosclerotic vascular disease and AF. 23 Further prospective studies are needed to evaluate the prognostic role of AF in the whole spectrum of symptomatic and asymptomatic patients with peripheral vascular disease.…”
Section: Quantitative Data Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Как демонстрирует один из анализов датского регистра, объединивший 11 480 больных ФП, перенесших ИМ или ЧКВ в период с 2000 по 2009 г., относительный риск кровотечений в первые 3 мес. лечения у пациентов, получавших варфарин в сочетании с аспирином и клопидогрелом, был в 1,47 раза выше, чем у пациентов, получавших аспирин и клопидогрел [3].…”
Section: варфарин в составе многокомпонентной антитромботической тераunclassified